Low Skilled adults' memories about their Physical Education Teachers. [Los recuerdos de adultos con baja competencia motriz sobre sus Profesores de Educación Física]. - Luis Miguel Ruiz-Pérez; Miguel Angel Gómez; Miriam Palomo-Nieto; José Antonio Navia-Manzano (Ramón Cantó Alcaraz, 2020)
The main purpose of this study was to analyze retrospectively the memories of a group of adults with low skills and the relationships between their memories and their physical education teachers during their school time. Ten adults (7 women and three men) participated in this study, aged between 25 and 56 years that declared to be low skilled during their school days. In order to carry out this study, a semi-strutured interview was conducted focusing the attention on obtaining memories of participants in their PE classes during their schoolage, and mainly their perceptions and feelings about their Primary and Secondary PE teachers. Results showed that the memories of behaviors and personality of their PE teachers were more important for participants than the learning from activities that their PE teachers taught. The feelings and emotions about his/her PE teachers were mostly negative, characterized by humiliation, abandonment, lack of help or indifference towards them. For these participants, their PE teachers did not live up to their needs. Knowing these memories had permitted the researchers to know a hidden part of the PE subject that is referred to a sector of the school population that shows low motor competence.